Model Kurikulum Pesantren Salafiyah dalam Perspektif Multikultural - Syafe'i, Imam (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2017)
Islamic boarding schools are one of the social religious institutions and Islamic education. In general, all pesantren must have characteristics that are not different, namely an institution whose leaders and caregivers are clerics. One type of boarding school in Indonesia is salafiyah boarding schools with special characteristics, namely salaf (traditional). The learning of classical Islamic books or often called "kitab kuning", is one of the characteristics of the salaf pesantren, especially the works of scholars who have embraced Syafi'iyah ideology which are indeed given in the scope of learning in traditional pesantren whose learning focuses on arrest harfiyah for a certain book (text). Santri is one part of the pesantren elements, there are various social and ethnic strata found in Indonesia, until now there has never been a clash of cultures or fights. An understanding of the views of the people in pesantren seems to have been implemented well, which is likely to be unfamiliar in their texts. The transformation of multicultural education has been integrated in the study of classical texts as well as sourced from normative sources found in the Qur'an and hadith, or through other learning such as PKN which has a multicultural educational content for pesantren which are formal education institutions. An understanding of diversity and eliminating Ika appear clearly in pesantren, there are no discriminatory practices for santri in the learning process or in everyday life, respecting so much ethnic diversity and differences, equality, tolerance and open attitude. Efforts to realize a national education goal through multicultural education / learning in Islamic boarding schools are based more on understanding holistic and constructive Islamic teachings.